2013
DOI: 10.1080/0312407x.2013.783604
|View full text |Cite
|
Sign up to set email alerts
|

Strengths And Struggles: Overseas Qualified Social Workers' Experiences In Aotearoa New Zealand

Abstract: A growing number of professionals practise in a country other than the one where they obtained their professional qualification. A mixed-methods study explored the experiences of one group of such professionals, overseas-qualified social workers practicing in New Zealand. This article reports findings from four key informant group interviews and an online survey (N 0294), including this population's satisfaction with their employment, their introduction to local practice, and experiences of mistreatment and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…Our research supports the case for enhancements in terms of the quantity and quality of supports for migrant social workers, as has been established in the existing scholarly literature (Brown et al, 2015;Bartley et al, 2012;Fouche et al, 2014b;Pullen-Sansfaçon et al, 2012). In addition, clearer guidance throughout the credential recognition process for migrant social workers would be beneficial.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our research supports the case for enhancements in terms of the quantity and quality of supports for migrant social workers, as has been established in the existing scholarly literature (Brown et al, 2015;Bartley et al, 2012;Fouche et al, 2014b;Pullen-Sansfaçon et al, 2012). In addition, clearer guidance throughout the credential recognition process for migrant social workers would be beneficial.…”
Section: Discussionsupporting
confidence: 64%
“…They recommend development of mentorship programs in combination with the implementation of several additional forms of support . Similarly, Fouche et al (2014b) discuss the need for better access to formal induction opportunities for migrant social workers. While these suggestions are a positive step forward in identifying the need for targeted supports for migrant social workers, current research lacks an explicit and detailed focus on how to support migrant social workers in gaining entry to the labour market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding suitable work was noted as a challenge in previous research for incoming transnational social workers (Fouché, Beddoe, Bartley, & Brenton, 2013;Papadopoulos, 2016) but this was not the experience of our outbound New Zealand social workers. Table 2 shows that most participants in this study found their first social work job in an overseas context within three months, and all had found social work employment by six months.…”
Section: Original Articlementioning
confidence: 92%
“…A social worker mobility research team based at the University of Auckland has conducted prior mixed methods studies of the overseas qualified workforce in Aotearoa New Zealand (Bartley, Beddoe, Fouch é, & Harington, 2012), experiences of migrant social workers in Aotearoa New Zealand (Bartley & Beddoe, 2018;Bartley et al, 2011;Fouché, Beddoe, Bartley, & de Haan, 2013; Fouch é, Bartley, Beddoe, & Brenton, 2013;Fouché, Beddoe, Bartley, & Parkes, 2015) and a small qualitative study of Aotearoa New Zealand social workers currently practising in the United Kingdom (UK) and Ireland (Beddoe & Fouché, 2014). Findings of the previous research have concluded that practising social work in a new context creates challenges and opportunities.…”
Section: Abstract: Transnational Social Workers; Global Workforce Mobmentioning
confidence: 99%